Isolation, Characterisation and Presumptive Identification of Lactic Acid Bacteria from Matoa (Pometia pinnata) Fruit - Rafli Zulfa Kamil; Dimas Anugrahillah; Heni Rizqiati; Fariz Nurmita Aziz; Rangga Wasi Hastrawirid (Journal of Applied Food Technology, 2026)
Each fruit has a distinct nutritional composition physicochemical characteristics, creating specific ecological niches for microbial growth. To the best of our knowledge, this study is the first to report the isolation and phenotypic characterisation of native LAB from matoa fruit, thereby providing baseline mircrobiological data for this underexplored fruit matrix. This research aims to isolate and characterise native LAB from matoa. The Matoa sample was inoculated into de Man-Rogosa-Sharpe (MRS) Broth and isolated using the streak plate method. The isolate was then characterised based on its morphological, physiological, and biochemical characteristics. Results shows that isolated LAB exhibit cream-coloured, circular colony morphology with clear edges, convex elevation, an opaque internal structure, and varying colony sizes. Cellular characteristics of the isolate included rod-shaped morphology, Gram-positive staining, non-catalase activity, and non-motility. The isolate survived at pH 5 and 6, 6.5% salt content, and at 25°C, 37°C, and 45°C. the The isolate also fermented glucose, sucrose, maltose, fructose, and galactose, and also did not produce H2S or indole. The LAB isolate was identified as belonging to the genus Lactobacillus and is presumably identified to be Lactobacillus plantarum.